2022
DOI: 10.1001/jamanetworkopen.2022.19535
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Food and Drug Administration Approval and Disparities in Immunotherapy Use Among Patients With Cancer in the US

Abstract: IMPORTANCE Clinical trials and compassionate use agreements provide selected patients with access to potentially life-saving treatments before approval by the Food and Drug Administration (FDA). Approval from the FDA decreases a number of access barriers; however, it is unknown whether FDA approval is associated with increases in the equitable use of novel therapies and reductions in disparities in use among patients with cancer in the US. OBJECTIVETo assess the association between FDA drug approval and dispar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In the past decades, anti-cancer immunotherapy has changed from a promising treatment method to a reality of clinical treatment. Many immunotherapy programs that can be used for patients with cancer have now been approved by the US FDA and European Medicines Agency and many other treatment programs are being studied as independent therapeutic interventions or in combination with clinical routine treatment ( 174 , 175 ). Treatment strategies are no longer based solely on interfering with metabolism of tumor cells or whether it is a purely clonal proliferative disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, anti-cancer immunotherapy has changed from a promising treatment method to a reality of clinical treatment. Many immunotherapy programs that can be used for patients with cancer have now been approved by the US FDA and European Medicines Agency and many other treatment programs are being studied as independent therapeutic interventions or in combination with clinical routine treatment ( 174 , 175 ). Treatment strategies are no longer based solely on interfering with metabolism of tumor cells or whether it is a purely clonal proliferative disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important albeit unsurprising finding, as it mirrors the known disparate access to care in HNC. While previous studies have found racial and ethnic disparities in access to immunotherapy in other cancer sites, our study makes a novel contribution by describing a potential disparity specific to HNC using clinical data. Of all cancers, HNC has the third-worst survival disparity between Black and White patients, and the disparate receipt of immunotherapy reported in this study illustrates how new therapeutics, while potentially effective, may inadvertently exacerbate already existing survival disparity .…”
Section: Discussionmentioning
confidence: 99%
“…An extensive literature has documented disparities in the receipt of different cancer treatments by race/ethnicity, SES, geographic location, and type of health insurance coverage, 34,[67][68][69][70][71][72][73] including studies showing disparities in the receipt of guideline-concordant treatment for many cancer types, such as cancers of the lung, 74,75 colorectum, 76,77 breast, 78,79 pancreas, 80,81 uterus, 82,83 ovary, 84,85 esophagus, 86 and head and neck. 87 Even if they receive cancer treatment, people of color and of lower SES are more likely to experience treatment delays, which can adversely affect the outcome.…”
Section: Disparities In Receipt Of Treatmentmentioning
confidence: 99%